2013
DOI: 10.1097/ta.0b013e3182a686a5
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of traumatic isolated sternal fracture and manubriosternal dislocation

Abstract: Therapeutic study, level IV; economic analysis, level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Mayberry et al [14] identified three key points for intervention as follows: (1) the presence of a sternal deformity, (2) the loss of sternal continuity for a period exceeding 6 weeks, and (3) the persistence of chest pain (between 2 and 8 weeks, in the opinion of most surgeons surveyed). Divisi et al [13] stated that possible injury to the underlying vascular structures must also be considered. Steel wire fixation is widely used in longitudinal sternotomy but often fails in horizontal fractures and nonunion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mayberry et al [14] identified three key points for intervention as follows: (1) the presence of a sternal deformity, (2) the loss of sternal continuity for a period exceeding 6 weeks, and (3) the persistence of chest pain (between 2 and 8 weeks, in the opinion of most surgeons surveyed). Divisi et al [13] stated that possible injury to the underlying vascular structures must also be considered. Steel wire fixation is widely used in longitudinal sternotomy but often fails in horizontal fractures and nonunion.…”
Section: Discussionmentioning
confidence: 99%
“…The steel wire sealing technique is suitable for longitudinal sternotomy, but most traumatic sternal fractures are transverse fractures or nonunions. In these cases, internal fixation with a titanium locking plate is a better choice [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…Rigid plate fixation has been shown to be an effective method of fixation of MSJ and other sternal fractures [2,7,10,11,13,14,19]. Ostensibly, the close proximity of vital organs directly abutting the dorsal surface of the sternum makes substantive bicortical constructs unfeasible.…”
Section: Discussionmentioning
confidence: 99%
“…A larger scale CT study of living patients with a normal age and equal gender distribution is warranted before areas of greatest screw purchase can be determined with certainty. In addition, the success of preliminary trials of rigid plate fixation for displaced MSJ and other sternal fractures show promise for development of an orthopedic standard for sternal fracture fixation [2,7,10,11,13,14,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, the diagnosis may be challenging as it would not be visible on routine chest X-ray films. It may be divided into sternal fracture and sternal dislocation, accounting for 7.5% and 2.9% of chest trauma patients (1). ISFs are mostly benign, but a sustained chest pain should arouse the suspicion of such a lesion.…”
Section: Introductionmentioning
confidence: 99%